Sodium Cholate‐Based Active Delipidation for Rapid and Efficient Clearing and Immunostaining of Deep Biological Samples. Issue 1 (5th November 2021) - Na, Myeongsu; Kim, Kitae; Oh, Kyoungjoon; Choi, Hyung Jin; Ha, ChangMan; Chang, Sunghoe
Abstract: Recent surges of optical clearing provided anatomical maps to understand structure‐function relationships at organ scale. Detergent‐mediated lipid removal enhances optical clearing and allows efficient penetration of antibodies inside tissues, and sodium dodecyl sulfate (SDS) is the most common choice for this purpose. SDS, however, forms large micelles and has a low critical micelle concentration (CMC). Theoretically, detergents that form smaller micelles and higher CMC should perform better but these have remained mostly unexplored. Here, SCARF, a sodium cholate (SC)‐based active delipidation method, is developed for better clearing and immunolabeling of thick tissues or whole organs. It is found that SC has superior properties to SDS as a detergent but has serious problems; precipitation and browning. These limitations are overcome by using the ion‐conductive film to confine SC while enabling high conductivity. SCARF renders orders of magnitude faster tissue transparency than the SDS‐based method, while excellently preserving the endogenous fluorescence, and enables much efficient penetration of a range of antibodies, thus revealing structural details of various organs including sturdy post‐mortem human brain tissues at the cellular resolution. Thus, SCARF represents a robust and superior alternative to the SDS‐based clearing methods and is expected to facilitate the 3D morphological mapping of various organs. Abstract : Sodium dodecyl sulfate (SDS) remains the first choice for active delipidation in tissue clearing methodologies. Detergents that form smaller micelles and higher critical micelle concentration should perform better but these remain unexplored due to technical limitations. By combining sodium cholate and an ion‐conductive film, SCARF overcomes these limitations, providing remarkably faster, superior tissue clearing and immunolabeling than SDS‐based methods.